We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
252
1
avatar+4322 

If \(f(3)=1\) and \(f(2x)=2f(x)\) for all \(x\) , find \(f^{-1}(64)\).

 Mar 10, 2018
 #1
avatar+103120 
+1

f(3)  =  1

f(6)  = f(2 * 3) = 2f(3)  = 2 * 1  = 2

f(12)  = f(2 * 6)  = 2f(6)  = 2 * 2  = 4

f(24)  = f(2 * 12) = 2f(12) = 2 * 4 = 8

f(48) = f(2 * 24)= 2f(24) = 2 * 8   = 16

f(96) = f(2 *48) = 2f(48) = 2 * 16 = 32

f(192) = f(2 * 96) = 2f(96) = 2 * 32  = 64

 

So

 

f(192)  =  64       which implies that

 

f-1(64)  =  192

 

 

cool cool cool

 Mar 10, 2018

32 Online Users

avatar
avatar